Optimizing The Number and Diameter of Piles to Enhance Foundation Resistance - Almajed, Rasool; Alabbas, Kadhim (Iraqi Journal of Civil Engineering, 2023)
ABSTRACTStudies in geotechnical engineering have the nonlinear behavior of soils. An experimental study was carried out on models of piled rafts, and four piles with a diameter of 25 mm and a length of (300, 400, and 500) mm were taken, with a raft of (180x180) mm, and compared with the piled-raft system of 180 × 180 raft and nine piles of 19 mm and 500 mm in diameter and length respectively. They were tested for raft resistance, number of piles, length, and diameter while maintaining the spacing between piles. Test results showed the raft performance improved by 76% when adding piles. The increase in the (L/D) ratio for variable (L) length leads to an increase in pile share of 87% for the groups (2×2). Also, pile share was increased by 10% with a decrease in the diameter of piles and an increase in the number of piles in the group. Therefore, the increment in each pile’s skin friction results in an increase in the bearing capacity of each pile.